Instructional methods for adolescents with learning and behavior problems - Schloss, Patrick J.; Smith, Maureen A.; Schloss, Cynthia N. (Boston : Allyn and Bacon, 1995)
This book is divided into three parts: Educational perspectives in secondary special education; General instructional approaches; and Instruction in basic and functional skills.
Keywords: Education; Learning disabled youth -- Education; Handicapped youth -- Education (Secondary); Special education -- Curricula